IMPROVING ENERGY EFFICIENCY IN AN AUTONOMOUS POWER SYSTEM USING RENEWABLE ENERGY SOURCES. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article will analyze and control optimal energy consumption of autonomous energy system of Kashkadarya region based on renewable energy sources. The goal set in the work is solved by mathematical modeling of linear programming methods, production rules and energy consumption modes through the production of consumers' living conditions. It is anticipated that energy consumers in the area under review will be able to independently cover the energy shortage by installing additional generating energy sources. The goal function is to minimize the financial costs for their energy consumption and maximize them from the export and redistribution of energy streams. Depending on the season in this study,